ARTEFACT MASQUERADING AS FIREARM AMMUNITION ON X-RAY - Tyagi, Ashish; Kumar, Hemant; Atal, Devinder Kumar; Yadav, Kapil (Journal of Forensic Medicine and Toxicology, 2019)
Postmortem Artefacts are often notorious in causing medico-legal complications during autopsies, which sometimes lead to misinterpretation of medico-legally significant antemortem findings and can wreck the investigation process. In periphery, most of the times due to lack of required expertise and infrastructure, the doctor conducting the autopsy fail to construe the artefacts because of which unwanted suspicion arises. When encountered such artefacts it can erroneously lead to false conclusions. So, the doctors have to draw conclusion logically and correctly and the autopsy pathologist should be able to distinguish them from significant antemortem changes. For those reasons these artefacts needs to be identified judiciously. Therefore, the role of autopsy surgeon is very crucial to identify these artefacts and aid in the justice. Here we’re presenting a case of radiological artefact which confused the autopsy surgeon initially as firearm ammunition and later on, on further evaluation found out to be a clothing accessory.
Keywords: Post Mortem Artefact; Autopsy; radiological artefact; charred; burns; firearm